2015
DOI: 10.1111/cod.12490
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to reactive diluents and hardeners in epoxy resin systems. IVDK data 2002–2011. Part II: concomitant reactions

Abstract: More detailed knowledge of cross-reactivity among ERS components facilitates the interpretation of patch test results and will allow safer ERSs to be composed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…In construction workers and painters, these reactions were associated with positive reactions to manifold hardeners and reactive diluents used in epoxy resin systems (Table S1). Concomitant reactions between aromatic glycidyl ethers might be explained by immunological cross‐reactivity 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In construction workers and painters, these reactions were associated with positive reactions to manifold hardeners and reactive diluents used in epoxy resin systems (Table S1). Concomitant reactions between aromatic glycidyl ethers might be explained by immunological cross‐reactivity 44 …”
Section: Discussionmentioning
confidence: 99%
“…Concomitant reactions between aromatic glycidyl ethers might be explained by immunological cross-reactivity. 44 Positive PT reactions to colophonium were documented in 4.2% of the patients (Table 3) and considered occupationally relevant in all handicraft professions with the exception of construction workers, and in an office clerk (Table 4). Abietic acid is the major allergen in colophonium and distilled tall oil, which is widely used in wbMWFs.…”
Section: Glues and (Epoxy) Resinsmentioning
confidence: 99%
“…In an IVDK analysis of all patch test reactions to epoxy resin and other components of epoxy resin systems between 2002 and 2011, 40% of patients sensitized to epoxy resin had a concomitant patch test reaction to glycidyl ethers 26 . This is roughly the same dimension as in the current study group (difference not significant).…”
Section: Discussionmentioning
confidence: 45%
“…A retrospective analysis of data from the Information Network of Departments of Dermatology (IVDK), 2002–2011, demonstrated that almost half of the patients sensitized to epoxy resin were additionally sensitized to reactive diluents or hardeners. Among the reactive diluents, 1,6-hexanediol diglycidyl ether was the most frequent contact allergen, followed by 1,4-butanediol diglycidyl ether (both often cross-react [ 125 ]), phenyl glycidyl ether, and p-tert -butylphenyl glycidyl ether. Among the hardeners, m-xylylene diamine (MXDA) and isophorone diamine (IPDA) were the most frequent contact allergens.…”
Section: Resultsmentioning
confidence: 99%